2001
DOI: 10.1203/00006450-200102000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase and Catalase Do Not Affect the Pulmonary Hypertensive Response to Group B Streptococcus in the Lamb

Abstract: The purpose of this study was to determine whether treatment with conjugated antioxidant enzymes could attenuate or abolish pulmonary hypertension induced by group B streptococcus (GBS). Lambs, 3-7 d old, were anesthetized and ventilated. Intravascular catheters were placed in the left ventricle, descending aorta, right atrium, and pulmonary artery for continuous monitoring of intravascular pressures. Cardiac output was measured with radiolabeled microspheres. Measurements were obtained at baseline and 15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In a lamb model of PPHN, Steinhorn et al (9) demonstrated that a single intratracheal dose of SOD reduced pulmonary vascular resistance and improved the pulmonary vasodilatory action of inhaled NO ⅐ . In contrast, Carpenter et al (10) did not observe changes in pulmonary vascular resistance after i.v. infusion of SOD in 3-to 7-d-old lambs.…”
mentioning
confidence: 82%
“…In a lamb model of PPHN, Steinhorn et al (9) demonstrated that a single intratracheal dose of SOD reduced pulmonary vascular resistance and improved the pulmonary vasodilatory action of inhaled NO ⅐ . In contrast, Carpenter et al (10) did not observe changes in pulmonary vascular resistance after i.v. infusion of SOD in 3-to 7-d-old lambs.…”
mentioning
confidence: 82%
“…After a 30-min recovery, either PEG diluted in 5 ml of normal saline (n ϭ 6, vehicle control) or PEG-SOD (n ϭ 7) was delivered through the left pulmonary artery catheter. The dose of PEG-SOD (1,000 -2000 U/kg every 6 h) was based upon previous studies that demonstrate a sustained significant increase in plasma SOD activity (8,32). Either PEG or PEG-SOD was given every 6 h to complete a total of four doses.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical fractionation procedures were linked in series to develop an initial purification protocol, which was modified to give the final protocol described here. At each step, fractions were assayed for pulmonary arterial hypertensive activity in 3-to 12-day-old lambs of Ϸ5 kg, as described (7). We previously demonstrated that pulmonary arterial pressure measurements were a valid surrogate for measurement of pulmonary vascular resistance in this animal model (7).…”
Section: Purification and Analysis Of Pulmonary Hypertensive Compoundmentioning
confidence: 99%
“…At each step, fractions were assayed for pulmonary arterial hypertensive activity in 3-to 12-day-old lambs of Ϸ5 kg, as described (7). We previously demonstrated that pulmonary arterial pressure measurements were a valid surrogate for measurement of pulmonary vascular resistance in this animal model (7). Fractions were infused peripherally into the femoral vein, not directly into the pulmonary artery.…”
Section: Purification and Analysis Of Pulmonary Hypertensive Compoundmentioning
confidence: 99%